THE EFFECT OF MANAGEMENT MORALITY ON ACCOUNTING FRAUD WITH INTERNAL CONTROL AS A MODERATING VARIABLE (STUDY IN PEMALANG REGENCY) - Pratomo Cahyo Kurniawan; Fika Azmi (Universitas Muhammadiyah Surakarta, 2019)
This study aims to examine the effect of management morality on the tendency of accounting fraud with internal control as a moderating variable. The research was conducted at the District Office of Pemalang. A common problem in this research is the occurrence of corruption cases that occurred with the amount of loss and the large number of personnel involved in the corruption case.The sampling technique used is total sampling by using all members of the population as a sample of 70 samples. Data collection techniques using questionnaires distributed to the finance and accounting department at the District Office Pemalang. The analysis technique used is multiple linear regression analysis.The results of the analysis show that management morality has a negative effect on the tendency of accounting fraud. Interaction test results show that there is a significant positive influence of internal control in the relationship between management morality and the tendency of accounting fraud, so that internal control is a moderating variable.